Strategi Meningkatkan Kerjasama Tim - Bayu Astapati Rahayu; Achmad Irfan Hadiyana; John Chaidir (Prosiding Amal Insani Foundation, 2023)
Teamwork in an organization is fundamental in an era that continues to change radically. Of course, this is a challenge for any organization because employees who can work well with the team that has been formed can be a competitive advantage for the organization. This research was conducted to determine the strategy in forming teamwork in an organization. The method used in this study is a quantitative method with the PLS-SEM approach. This research was conducted at PT. Indah Kiat Pulp & Paper Product Tbk in the QC section. The data collection method is by questionnaire and using the SmartPLS version 4 analysis tool. The results show that transformational leadership and work motivation partially positively and significantly affect teamwork.